UNSUR BUDAYA CERITA RAKYAT SUKU MAIRASI - Sriyono Sriyono; Siswanto Siswanto (ppjbsip, 2022)
Abstract : The study aims to reveal elements of the culture reflected in the mairasi, kaimana, west Papua folk story with the approach to literary anthropology. Data obtained through observation, interview, record, and note. Research data consists of textual units containing cultural elements. Analysis is done by interpreting these cultural elements based on ethnographic reference. The results of this study suggest that through the literary anthropology approach, the cultural elements of the Mairasi folklore become much clearer. Analysis found that the Mairasi language is alive and is used as a means of communication. The Mairasi people had a traditional house called weso and became a garden home. This house also as a kinship marker. The mairasi people know the nuclear family and the marriage is performed with the klen outside their klen. To maintain stability and cultural norms they have a chosen leader based on his knowledge of klen background. The Mairasi people became familiar with the new profession of fishing, originally they were hunters and farmers. Some devices used for daily activities are more commonly made from natural materials. It is the reasons that they believe in natural forces which are internalized in their systems of knowledge and religious systems.